Relationships of mechanical properties for concrete containing crumb rubber as partial replacement to fine aggregate - Mohammed B.S.; Hossain K.M.A.; Azmi N.J. (2023)
Several research works have been carried out to study the fresh and hardened properties of concrete containing crumb rubber (rubbercrete) as a replacement of fine aggregate. The outcomes of these studies have highlighted the advantages and disadvantages of rubbercrete compared with conventional concrete mixtures. Rubbercrete is being used in the construction industry for a variety of purposes and the establishment of valid relationships among its various mechanical properties is worthwhile. Fourty five mixtures with different slump level, water to cementitious material ratio (w/c) and crumb rubber content were prepared, cast and tested. Empirical relationships among compressive strength, flexural strength, splitting tensile strength and modulus elasticity were established at the age of 28 days based on regression analyses.